A molybdenum-doped argyrodite-type sulfide electrolyte and a preparation method thereof

The molybdenum-doped sulfur-silver germanium ore-type sulfide electrolyte solves the problem of poor chemical stability of electrolytes in the prior art, achieves higher ionic conductivity and electrochemical stability, and promotes the application of high-performance solid-state batteries.

CN114883642BActive Publication Date: 2025-04-01SHANGHAI FIRM LITHIUM NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202210519946.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-13
Publication Date
2025-04-01
Estimated Expiration
2042-05-13

AI Technical Summary

Technical Problem

In the prior art, electrolytes have poor chemical stability and are difficult to meet the needs of high-performance solid-state batteries.

Method used

The sulfhydryl silver germanium ore-type sulfide electrolyte doped with molybdenum has a chemical composition of Li6+2xMoxP1-xS5Cl, of which 0

Benefits of technology

It significantly improves the ionic conductivity and electrochemical stability of the electrolyte and promotes the practical application development of high-performance solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114883642B_ABST
    Figure CN114883642B_ABST
Patent Text Reader

Abstract

The present invention relates to a molybdenum-doped argyrodite-type sulfide electrolyte and a preparation method thereof. The argyrodite-type sulfide solid electrolyte and a preparation method thereof of the present invention belong to the technical field of battery materials. The chemical general formula of the sulfide electrolyte in the product developed by the present invention is: Li 6+2x Mo x P 1‑x S5Cl, where 0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and in particular relates to a molybdenum-doped argyrodite-type sulfide electrolyte and a preparation method thereof. Background Art

[0002] In modern society, human beings have an increasing demand for energy, while the limited reserves of traditional fossil energy and the huge pollution caused to the environment have made people pay more attention to new clean and renewable energy (wind energy, solar energy, hydropower, etc.). However, the storage of renewable energy requires large-scale energy storage equipment. Among them, lithium-ion batteries are a very mature energy storage device and have been widely used in various fields of social life. However, traditional lithium-ion batteries are prone to the risk of combustion and explosion, which poses a great safety hazard. All-solid-state lithium batteries use solid electrolytes instead of liquid organic electrolytes, which improves the safety of the battery and also increases the energy density of the battery. Therefore, the research and development of solid electrolyte materials is urgent and important.

[0003] Sulfide electrolytes, as an important component of inorganic solid electrolytes, have high ionic conductivity and stable electrochemical window. The grain boundary impedance of the electrolyte can be reduced by cold pressing, which is of great significance for the application of all-solid-state lithium-sulfur batteries (ASSLSB). As we all know, LPSC has high ionic conductivity and has great application advantages in all-solid-state lithium batteries. Mo is doped in it to explore a solid electrolyte material with high ionic conductivity and good chemical stability. Summary of the invention

[0004] The purpose of the present invention is to provide a molybdenum-doped argyrodite-type sulfide electrolyte and a preparation method thereof in order to address the problem of poor chemical stability of electrolytes in the prior art. The product obtained by the present invention has higher ionic conductivity, thereby accelerating the practical application development of high-performance solid-state batteries.

[0005] The purpose of the present invention can be achieved by the following scheme:

[0006] The present invention provides a molybdenum-doped argyrodite-type sulfide electrolyte, wherein the chemical composition of the argyrodite-type sulfide electrolyte is Li 6+2x Mo x P 1-x S5Cl, where 0 <x<0.5。

[0007] Furthermore, Li 6+2x Mo x P 1-x In S5Cl, 0 <x<0.3。

[0008] The present invention also provides a method for preparing a molybdenum-doped argyrodite-type sulfide electrolyte, and the preparation method includes the following steps:

[0009] S1. According to the general formula: Li 6+2x Mo x P 1-x S5Cl, where 0 < x < 0.5, weigh out stoichiometric ratios of Cl source, Li source, S source, P source, and Mo source, mix and ball-mill to obtain solid electrolyte powder;

[0010] S2. Press the solid electrolyte powder into a solid electrolyte sheet;

[0011] S3. Vacuum sinter the solid electrolyte sheet to obtain a molybdenum-doped argyrodite-type sulfide electrolyte.

[0012] Further, in step S1, the Cl source is selected from LiCl.

[0013] Further, in step S1, the Li source is selected from at least one of LiH, Li2S2, and Li2S.

[0014] Further, in step S1, the S source is selected from at least one of S, H2S, P2S5, Li2S2, and Li2S.

[0015] Further, in step S1, the P source is selected from at least one of P, P2S5, P4S9, P4S3, and P4S6.

[0016] Further, in step S1, the Mo source is selected from at least one of (NH4)2MoO4, Mo2S3, and MoO3.

[0017] Further, step S1 is carried out in argon. Prepare the raw materials in a glove box filled with argon, mix them thoroughly to obtain a mixture powder, then seal it in a ball-milling jar to avoid contact with air. Place the ball-milling jar on a planetary ball mill to mix and obtain preliminary solid electrolyte powder.

[0018] Further, in step S1, the rotation speed of the ball milling is 500 - 600 r.p.m, and the ball milling time is 5 - 30 h. The ball milling and mixing adopt the method of first manual grinding and then mechanical ball milling. The manual grinding time is 15 - 30 min. The mechanical ball milling uses a planetary ball mill.

[0019] Further, in step S2, before pressing, the precursor powder is pre-screened using a sieve with a size of 600 - 1200 mesh.

[0020] Further, in step S2, the pressure for pressing is 300 - 500 MPa. Excessive pressure will cause Li +The diffusion resistance in the battery increases, resulting in poor mechanical properties. Too little pressure will cause rapid capacity decay and affect performance.

[0021] Furthermore, the thickness of the solid electrolyte sheet in step S2 is 300-700 μm. If the electrolyte is too thick, the mass ratio is too high, that is, the ratio of inactive materials is too high, which will reduce the energy density of the whole battery; if the electrolyte is too thin, lithium dendrites can easily pierce the electrolyte and cause a short circuit.

[0022] Furthermore, in step S3, the temperature of vacuum sintering is 350-700°C, and the sintering time is 3-10h. The rate of temperature increase during sintering is 0.5-5°C / min. After sintering, the temperature is lowered to room temperature at a rate of 0.5-5°C / min. The reaction calcination temperature is too low, and the reaction is insufficient; as the temperature increases, the grain size increases, which is conducive to the enhancement of densification. However, when the sintering temperature is too high, the irregular particles have a larger space due to the increase in size, which reduces the density. And when the temperature is too high, anisotropic thermal expansion causes material stress, causing voids and cracks in the material. As a result, the mobility of lithium ions is limited by larger grain boundaries, which is not conducive to obtaining higher conductivity. Too fast or too slow a heating rate will cause the water vapor and oxygen in the quartz tube to not fully volatilize, affecting the performance of the electrolyte.

[0023] Furthermore, the vacuum pressure of the vacuum sintering in step S3 is less than 10 -4 Pa.

[0024] Furthermore, the weighing, mixing, ball milling, grinding, screening and pressing in steps S1 to S3 are all carried out under the protection of an inert atmosphere.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The argyrodite-type sulfide electrolyte prepared by the present invention has higher ionic conductivity and good electrochemical stability.

[0027] (2) The product obtained by the present invention has higher ionic conductivity, thereby accelerating the practical application development of high-performance solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0029] Figure 1 This is the EIS impedance diagram of the solid electrolyte prepared in Example 1;

[0030] Figure 2 This is the XRD pattern of the solid electrolyte prepared in Example 1. Detailed Embodiments

[0031] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments. The following examples are implemented on the premise of the technical solution of the present invention, providing detailed implementation manners and specific operation processes, which will help those skilled in the art to further understand the present invention. It should be noted that the protection scope of the present invention is not limited to the following embodiments. Several adjustments and improvements made on the premise of the concept of the present invention all fall within the protection scope of the present invention.

[0032] According to one aspect of the present invention, the present invention provides a argyrodite-type sulfide electrolyte and a preparation method thereof. According to an embodiment of the present invention, it includes:

[0033] (1) Prepare raw materials in a glove box filled with argon, mix them充分混合, obtain a mixture powder and then seal it in a ball milling jar to avoid contact with air;

[0034] (2) Place the ball milling jar on a planetary ball mill for mixing to obtain a preliminary solid electrolyte powder;

[0035] (3) Press the solid electrolyte powder obtained in step (2) into a solid electrolyte sheet under a pressure of 350 MPa;

[0036] (4) Package the obtained solid electrolyte in a quartz tube, and the vacuum sealing pressure of the tube is 10 -4 Pa

[0037] (5) Subject the quartz tube in (4) to high-temperature sintering treatment in a muffle furnace, and obtain an argyrodite-type sulfide electrolyte after cooling.

[0038] Thus, the present invention prepares an argyrodite-type sulfide solid electrolyte Li 6+2x Mo x P 1- x S5Cl by ball milling and sintering, where 0 < x < 0.5. The product obtained by the present invention has higher ionic conductivity and good electrochemical stability.

[0039] According to a specific embodiment of the present invention, the Li source used for preparing the raw materials can be at least one selected from materials such as LiH, Li2S2, Li2S, etc. Thus, an argyrodite-type sulfide solid electrolyte with higher ionic conductivity can be effectively prepared.

[0040] According to a specific embodiment of the present invention, the S source used for preparing the raw materials can be at least one selected from materials such as S, H2S, P2S5, Li2S2, Li2S, etc. Thus, an argyrodite-type sulfide solid electrolyte with higher ionic conductivity can be effectively prepared.

[0041] It should be noted that the phrase "充分混合" in the original text seems to be an incomplete expression. I translated it as "mix them充分混合" to maintain the integrity of the original text. You may need to check and correct it according to the actual situation.According to a specific embodiment of the present invention, the P source used in the above-mentioned raw material preparation can be at least one selected from P, P2S5, P4S9, P4S3, P4S6, etc. Thus, a argyrodite-type sulfide solid electrolyte with higher ionic conductivity can be effectively prepared.

[0042] According to a specific embodiment 1 of the present invention, in step (2), under the protection of an inert gas, Li2S, Mo2S3, LiCl and P2S5 are premixed in a molar ratio of 2.575:0.0375:1:0.4625.

[0043] According to a specific embodiment of the present invention, the ball milling mixing in step (2) is performed by first manual grinding and then mechanical ball milling. The manual grinding time is 15-30 minutes, preferably the manual grinding time is 20 minutes, 22 minutes, 25 minutes, and 30 minutes. The abrasive thus formed is evenly dispersed and has a moderate particle size.

[0044] According to a specific embodiment of the present invention, the ball milling mixing in step (2) is performed by first manual grinding and then mechanical ball milling. The mechanical ball milling adopts a planetary ball mill with a rotation speed of 500-600 rpm, specifically 500 rpm, 550 rpm, 570 rpm, 600 rpm. Preferably, the ball milling speed is set to 550 rpm, 570 rpm, 600 rpm. The ball milling time is set to 5-30 h. Specifically, it can be 5 h, 7 h, 9 h, 10 h, 15 h, 20 h, 25 h, 30 h, preferably, the ball milling time is 20 h, 25 h, 30 h. The abrasive thus formed is evenly dispersed and has a moderate particle size, which meets the requirements for preparing argyrodite-type sulfide solid electrolytes.

[0045] According to a specific embodiment of the present invention, in step (3), the precursor powder is pre-screened with a sieve of 600-1200 mesh before tableting. Specifically, it can be 600 mesh, 700 mesh, 800 mesh, 900 mesh, 1000 mesh, 1100 mesh, 1200 mesh. The pressing pressure is 300-500MPa, specifically 300MPa, 320MPa, 350MPa, 370MPa, 400MPa, 420MPa, 450MPa, 470MPa, 500MPa. Preferably, the pressing pressure is 450MPa, 470MPa, 500MPa. The embryo body formed by the pressing is of moderate size, which is convenient for subsequent sintering in a quartz tube.

[0046] According to a specific embodiment of the present invention, in step (5), the temperature is raised to 350 - 700 °C at a heating rate of 0.5 - 5 °C / min. The heating rate can specifically be 0.5 °C / min, 1 °C / min, 1.5 °C / min, 2 °C / min, 2.5 °C / min, 3 °C / min, 3.5 °C / min, 4 °C / min, 4.5 °C / min, 5 °C / min. Preferably, the temperature is raised to 475 - 525 °C at a heating rate of 1 - 2 °C / min, whereby the proportion of the crystalline phase in the argyrodite-type sulfide solid electrolyte can be increased to a greater extent and the proportion of the amorphous phase can be reduced.

[0047] According to a specific embodiment of the present invention, the sintering time in step (5) is 3 - 10 h. In step (5), the temperature is lowered to room temperature at a rate of 0.5 - 5 °C / min. Specifically, the sintering time is 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h. Preferably, the sintering time is 8, 9, 10 h, and the cooling rate is 1 - 2 °C / min, whereby the proportion of the crystalline phase in the argyrodite-type sulfide solid electrolyte can be increased to a greater extent and the proportion of the amorphous phase can be reduced.

[0048] According to a specific embodiment of the present invention, steps (1) - (5) of weighing, mixing evenly, ball milling, grinding and sieving, pressing, sealing in a vacuum quartz tube, and high-temperature sintering in a muffle furnace are all carried out under the protection of an inert atmosphere.

[0049] According to a specific embodiment of the present invention, the thickness of the argyrodite-type sulfide electrolyte is 300 - 700 μm. For example, it can be 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 550 μm, 600 μm, 650 μm, 700 μm. Preferably, the thickness of the argyrodite-type sulfide electrolyte is 300 μm

[0050] Another object of the present invention is to prepare an argyrodite-type sulfide solid electrolyte Li 6+2x Mo x P 1-x S5Cl, where 0 < x < 0.5. According to an embodiment of the present invention, this argyrodite-type sulfide solid electrolyte is prepared by the method for preparing an argyrodite-type sulfide solid electrolyte in the previous embodiments. Since in the above method, the raw materials are manually ground and mixed in a glove box filled with an inert gas and then put into a ball mill jar for ball milling; then the ball-milled sample is pressed into a tablet; and finally, the target sulfide solid electrolyte is obtained through sintering treatment. The product obtained by the present invention has higher ionic conductivity and better electrochemical stability.

[0051] Example 1

[0052] The preparation steps of a modified argyrodite-type sulfide electrolyte are as follows:

[0053] (1) In a glove box filled with argon, Li2S, Mo2S3, LiCl, and P2S5 were premixed in a molar ratio of 2.575:0.0375:1:0.4625 to prevent them from contacting with air.

[0054] (2) The sealed ball mill jar was fixed on a planetary ball mill and ball milled at a speed of 550 rpm for 16 h.

[0055] (3) The solid electrolyte powder obtained in step (2) was pressed into a sheet in a glove box at a pressure of 350 MPa and a thickness of 500 μm.

[0056] (4) The initial solid electrolyte sheet obtained in step (3) is placed in a quartz tube or a glass tube and sealed under vacuum at a vacuum pressure of 1×10 -4 Pa.

[0057] (5) The quartz tube or glass tube sealed in step (4) is placed in a muffle furnace for sintering for 10 hours at a temperature of 600°C and a heating and cooling rate of 0.5°C / min -1 .

[0058] (6) The composition is Li 6.15 Mo 0.075 P 0.925 S5Cl sulfide solid electrolyte, the electrolyte powder is placed in a tablet pressing mold and pressed into a solid electrolyte sheet. Then the positive electrode sheet is placed on one side of the solid electrolyte and pressed with pressure. Finally, a lithium sheet is attached to the other side of the solid electrolyte and pressed into an all-solid-state battery.

[0059] The conductivity of the solid electrolyte prepared in Example 1 is 1.2×10 -4 S / cm, EIS impedance diagram Figure 1 As shown, the XRD spectrum is Figure 2 shown.

[0060] Example 2

[0061] The preparation steps of a modified argyrodite-type sulfide electrolyte are as follows:

[0062] (1) Li2S, Mo2S3, LiCl, and P2S5 were premixed in a molar ratio of 2.55:0.025:1:0.475 in a glove box filled with argon to prevent them from contacting with air.

[0063] (2) The sealed ball mill jar was fixed on a planetary ball mill and ball milled at a speed of 550 rpm for 16 h.

[0064] (3) The solid electrolyte powder obtained in step (2) was pressed into a sheet in a glove box at a pressure of 350 MPa and a thickness of 500 μm.

[0065] (4) The initial solid electrolyte sheet obtained in step (3) is placed in a quartz tube or a glass tube and sealed under vacuum at a vacuum pressure of 1×10 -4 Pa.

[0066] (5) Place the sealed quartz tube or glass tube in step (4) in a muffle furnace and sinter for 12 hours at a temperature of 550°C, with a heating and cooling rate of 0.5°C / min -1 .

[0067] (6) The composition is Li 6.1 Mo 0.05 P 0.95 S5Cl sulfide solid electrolyte, the electrolyte powder is placed in a tablet pressing mold and pressed into a solid electrolyte sheet, then the positive electrode sheet is placed on one side of the solid electrolyte and pressed under pressure, and finally a lithium sheet is attached to the other side of the solid electrolyte to press into an all-solid-state battery. The conductivity of the solid electrolyte prepared in Example 2 is 1.1×10 -4 S / cm.

[0068] Comparative Example 1

[0069] A modified sulfide electrolyte, the preparation steps are basically the same as those in the embodiment, and the raw materials are Li2S, LiCl, and P2S5 with a molar ratio of 2.5:1:0.5.

[0070] A solid electrolyte composed of Li6PS5Cl sulfide was obtained, and the electrolyte powder was placed in a tablet pressing mold and pressed into a solid electrolyte sheet. Then, the positive electrode sheet was placed on one side of the solid electrolyte and pressed under pressure. Finally, a lithium sheet was attached to the other side of the solid electrolyte and pressed into an all-solid-state battery. The conductivity of the obtained solid electrolyte is 0.9×10 -4 S / cm.

[0071] Comparative Example 2

[0072] A modified sulfide electrolyte, the preparation steps are basically the same as those in Example 1, the raw materials are Li2S, Mo2S3, LiCl, P2S5 in a molar ratio of 3:0.25:1:0.25, and the composition is Li7Mo 0.5 P 0.5S5Cl sulfide solid electrolyte, the electrolyte powder is placed in a tablet pressing mold and pressed into a solid electrolyte sheet, then the positive electrode sheet is placed on one side of the solid electrolyte and pressed with pressure, and finally a lithium sheet is attached to the other side of the solid electrolyte to press into a full solid-state battery. At this time, the Mo content has exceeded the optimal performance limit, and the conductivity drops sharply, with a conductivity of 0.7×10 -4 S / cm.

[0073] Comparative Example 3

[0074] A modified sulfide electrolyte, the preparation steps are basically the same as those in Example 1, except that: the pressure applied to the tablet pressing mold is too large, which is 600 MPa.

[0075] The composition is Li 6.15 Mo 0.075 P 0.925 S5Cl sulfide solid electrolyte, the electrolyte powder is placed in a tablet pressing mold and pressed into a solid electrolyte sheet, then the positive electrode sheet is placed on one side of the solid electrolyte and pressed with pressure, and finally a lithium sheet is attached to the other side of the solid electrolyte to press into a full solid-state battery. The battery performance obtained in the end is very poor, and the conductivity of the prepared solid electrolyte is 0.3×10 -4 S / cm.

[0076] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing a molybdenum-doped argyrodite-type sulfide electrolyte, characterized in that: The chemical composition of the electrolyte is Li 6+2x Mo x P 1-x S5Cl, where 0.05 < x < 0.075; The preparation method includes the following steps: S1, according to the general formula: Li 6+2x Mo x P 1-x S5Cl weigh Cl source, Li source, S source, P source and Mo source in stoichiometric ratio, mix and ball-mill to obtain solid electrolyte powder; S2, pressing the solid electrolyte powder into a sheet to obtain a solid electrolyte sheet; S3, vacuum sintering the solid electrolyte sheet to obtain a molybdenum-doped argyrodite-type sulfide electrolyte; In step S1, the Cl source is selected from LiCl; the Li source is selected from at least one of LiH, Li2S2, and Li2S; the S source is selected from at least one of S, H2S, P2S5, Li2S2, and Li2S; the P source is selected from at least one of P, P2S5, P4S9, P4S3, and P4S6; the Mo source is selected from at least one of (NH4)2MoO4, MoO3, and Mo2S3; The tableting pressure in step S2 is 300-500 MPa.

2. The preparation method according to claim 1, characterized in that: Step S1 is performed in argon gas.

3. The preparation method according to claim 2, characterized in that: In step S1, the ball milling speed is 500-600 rpm, and the ball milling time is 5-30 hours.

4. The preparation method according to claim 1, characterized in that: In step S2, the precursor powder is sieved using a sieve with a size of 600-1200 mesh before tableting.

5. The preparation method according to claim 1, characterized in that: The thickness of the solid electrolyte sheet in step S2 is 300-700 μm.

6. The preparation method according to claim 1, characterized in that: The vacuum sintering temperature in step S3 is 350-700° C., and the sintering time is 3-10 hours.

7. The preparation method according to claim 1, characterized in that: The heating rate during sintering is 0.5-5℃ / min.

Citation Information

Patent Citations

  • Doped phosphorus-sulfur iodide solid electrolyte and preparation method and application thereof

    CN111092262A

  • Argyrodite type sulfide solid electrolyte containing lithium halide coating layer and preparation of argyrodite type sulfide solid electrolyte

    CN114267874A

Cited By

  • Lithium argyrodite-based complex-phase solid electrolyte material as well as preparation method and application of lithium argyrodite-based complex-phase solid electrolyte material

    CN120854663A

  • A lithium-sulfur silver-germanium mineral-based multiphase solid electrolyte material, its preparation method and application

    CN120854663B